Augmented Criminality – How Mobile Augmented Reality Crime Overlays Affect People’s Sense of Place - Liao, Tony Chung-Li; Yang, Hocheol; Lee, Songyi; Xu, Kun; Feng, Ping; Bennett, Spencer (AoIR Selected Papers of Internet Research, 2016)
Communication about real-life crime and space has long been an important question for sociologists, criminologists, and policymakers alike. With federal laws like the Clery Act mandating disclosure of crime information on college campuses, many colleges have been turning to mobile technologies and text messaging to alert populations to crime. This study examines the latest development in display technology, specifically augmented reality technologies, to explore how digital overlays of crime information affect people's sense of place/space. Because augmented reality applications can literally overlay crime information on top of place, it is important to understand how that visual representation can alter people's perceptions and emotions of their physical surroundings. Through an experimental design (N=80) where participants are randomly assigned to an augmented reality condition or a text message condition and asked to fill out qualitative questionnaires about their perception of that place, this study examines how augmented reality crime displays can alter people's perceptions of place, affect people's imaginations and projections of the crimes that take place, and affect people's emotional response to place.